Innovation And Development Of Dash Instruments For Functional Examination Of The Hand In Brachialis Plexus Injury (BPI) - Endang Sri Wahyuni; Retna Febri Arifiati (Poltekkes Kemenkes Surakarta, 2022)
Background: The modified DASH instrument has been used as a measure of the functional ability of the hand in brachial plexus injury (BPI) until now, but its validity and reliability have not been tested. The aims of the study are to analyze the validity and reliability of the modified DASH instrument as a measure of the functional ability of the hand in brachial plexus injury (BPI) conditions. Methods: This research uses an observational correlation approach. The design of the validity and reliability test uses the person-product moment test and Cronbach's alpha based on standardized items. The number of questions is 30, with 75 research subjects selected by purposive sampling. Results: The majority of the research subjects were male, 56 subjects (74.7%), were in the late adolescent age group (17–25 years) of 46.7% (35 subjects). Construct validity test value > 0.227 with ρ < 0.05. The instrument reliability coefficient value is 0.925 with Cronbach's Alpha on each question item worth above 0.90. Conclusion: All Q1-Q30 question items are valid and reliable so they can be used to measure hand functional abilities under BPI conditions.